Is the capture of invertebrate prey by the aquatic carnivorous plant Utricularia australis selective?. (4th March 2022) - Ceschin, S.; Bellini, A.; Salituro, A.; Traversetti, L.; Ellwood, N. T. W.
Abstract: Utricularia (bladderwort) trap contents have frequently been used to define its diet, but there is a scarcity of information on prey availability. Yet making comparisons between trap contents and outside communities could help define feeding strategies of these fascinating carnivorous plants. This study focuses on U. australis, the most common aquatic bladderwort in central Italy, with data of inside- and outside-trap communities from 23 sites. The feeding strategy of U. australis is highly dependent on prey availability and size; the prey has to be large enough to stimulate trap triggering, yet small enough to be taken up through the trap door unimpeded. In addition, the prey has to be moderately motile but not dispersive. The trap contents were generally a mixture of species taken up by active and spontaneous trap firing. Stimulation of a heavy epiphytic growth by Utricularia resulted in higher entrapment of epiphyte-grazing taxa resulting in a positive feedback loop. The comparative data here also suggest that prey digestion is a rapid enough process that keeps up with the seasonal succession of the outside community. The trapped community (or the diet) of U. australis seems to derive by the contribution of all these factors.